Recent Progress in (Photo-)-Electrochemical Conversion of CO2 With Metal Porphyrinoid-Systems - Dedić, Dženeta; Dorniak, Adrian; Rinner, Uwe; Schöfberger, Wolfgang (Frontiers in Chemistry, 2021)
Since decades, the global community has been facing an environmental crisis, resulting in the need to switch from outdated to new, more efficient energy sources and a more effective way of tackling the rising carbon dioxide emissions. The activation of small molecules such as O2, H+ and CO2 in a cost- and energy-efficient way has become one of the key topics of catalysis research. The main issue concerning the activation of these molecules is the kinetic barrier that has to be overcome in order for the catalyzed reaction to take place. Nature has already provided many pathways in which small molecules are being activated and changed into compounds with higher energy levels. One of the most famous examples would be photosynthesis in which CO2 is transformed into glucose and O2 through sunlight, thus turning solar energy into chemical energy. For these transformations nature mostly uses enzymes that function as catalysts among which porphyrin and porphyrin-like structures can be found. Therefore, the emphasis of research are molecules such as porphyrins and its structural relatives like corroles or phthalocyanines whose metal-complexes have been used for multiple catalytic transformations. For example the cobalt(III)triphenylphosphine corrole complex has been used as a catalyst for the electroreduction of CO2 to ethanol and methanol. The overall goal and emphasis of this research area is to develop a method for industrial use, raising the question of whether and how to incorporate the catalyst onto supportive materials. Graphene oxide, multi-walled carbon nanotubes, carbon black and activated carbon, to name a few examples, have become researched options. These materials also have a beneficial effect on the catalysis through for instance preventing rival reactions such as the HER (Hydrogen Evolution Reaction) during CO2 reduction. It is very apparent that the topic of small molecule activation offers many solutions for our current energy as well as environmental crises and is becoming a thoroughly investigated research objective. This review article aims to give an overview over recently gained knowledge and should provide a glimpse into upcoming challenges relating to this subject matter.